2011
DOI: 10.1039/c1dt10588d
|View full text |Cite
|
Sign up to set email alerts
|

Origins of stereoselectivity in optically pure phenylethaniminopyridine tris-chelates M(NN′)3n+ (M = Mn, Fe, Co, Ni and Zn)

Abstract: One-pot reactions of 2-pyridinecarboxaldehyde, chiral phenylethanamines and Fe(II) give single diastereomer fac diimine complexes at thermodynamic equilibrium so that no chiral separations are required (d.r. > 200 : 1). The origins of this stereoselectivity are partly steric and partly a result of the presence of three sets of inter-ligand parallel-offset π-stacking interactions. Mn(II), Co(II), Co(III), Ni(II) and Zn(II) give similar fac structures, alongside the imidazole analogues for Fe(II). While most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
82
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 71 publications
9
82
0
Order By: Relevance
“…The single "conventional" phenyl/pyridine -stack has a centroid-centroid distance of ca 3.60 Å, within the range we have reported previously. 28 The two -stacks between phenyl and 2,2'-bipyridine rings may be described by two such centroid-centroid distances: a shorter at 3.60-3.69 Å and a longer of 4.41-4.60 Å. The rings are close to parallel (ca 5˚) with interplanar distances of ca 3.38 Å, significantly shorter than those computed by Grimme for similar scenarios (ca 3.5 Å).…”
Section: Design Synthesis and Characterisationmentioning
confidence: 78%
See 2 more Smart Citations
“…The single "conventional" phenyl/pyridine -stack has a centroid-centroid distance of ca 3.60 Å, within the range we have reported previously. 28 The two -stacks between phenyl and 2,2'-bipyridine rings may be described by two such centroid-centroid distances: a shorter at 3.60-3.69 Å and a longer of 4.41-4.60 Å. The rings are close to parallel (ca 5˚) with interplanar distances of ca 3.38 Å, significantly shorter than those computed by Grimme for similar scenarios (ca 3.5 Å).…”
Section: Design Synthesis and Characterisationmentioning
confidence: 78%
“…Recently we showed that by linking two diastereomerically pure tris-chelate metal complex units [28][29][30][31] via the groups X [Fig 1(d)] we could access water-compatible, stereochemically inert, functionalised helices we called flexicates. 32,33 These compounds are highly symmetrical, with the general structure of Fig1(a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The free energy penalty of 38 k B T for ( S )‐ b lies in the limiting regime of a large f 1  value, where the sergeant‐and‐soldiers effect is overwhelming and the chiroptical response is insensitive to the exact value (Figure S8). Between ( S )‐ c and ( S )‐ d , ( S )‐ d exhibited a stronger ability to control the configuration at the metal center, which we attribute to the greater bulk of the side group (cyclohexyl versus isopropyl) 16a, 17. We infer that both sterics and π‐stacking effects between phenyl and pyridyl rings are responsible for the strong influence of amine ( S )‐ b upon the metal‐centered configuration 16a…”
mentioning
confidence: 93%
“…Remarkably, no amplification was observed for Zn II : the excess chirality of the Zn II L 3 complex 4 b increased linearly as a function of added ( S )‐ b . These observations can be understood in terms of the increased metal–ligand distance when going from Fe II through Co II to Zn II ,16a with a concomitant reduction in bond strength (see Section S5 in the Supporting Information), which in turn decreases the steric gearing of the chiral amine residues required for effective stereochemical control around the metal center.…”
mentioning
confidence: 99%